Analysis of Green Brand Image on Green Brand Equity With Green Trust, Green Satisfaction, And Green Perceived Value As Mediation - Vilaningrum Wadyatenti, M.A. Diva; Pranatasari, Fransisca Desiana (Dinasti Publisher, 2025)
People are starting to recognize that using green products daily is a crucial step in solving the global environmental crisis. The concept behind green marketing is to develop green brands and green products. This study investigates the influence of green brand image on green brand equity. In addition, it is also to examine the impact of green brand image on green brand equity mediated by green trust, green satisfaction, and green perceived value. It is a quantitative study. A self-administered survey was used to collect data. The sampling method uses non-probability sampling techniques. The sampling technique used is purposive sampling with 196 respondents. In this study, the Partial Least Square (PLS) data analysis technique was used. The outer model analysis was measured using validity tests, and the structural model is an analytical step to test a hypothesis. The results of this study show that Green Brand Image directly affects Green Brand Equity. Green Brand Image affects Green Brand Equity by partially mediating Green Trust, Green Satisfaction, and Green Perceived Value.